Acupuncture related acute purulent pericarditis masquerading uremic pericarditis - Waqas Ullah; Sohaib Roomi; Zeeshan Sattar; Asrar Ahmad; Zain Ali; Usman Sarwar; Vincent Figueredo (Greater Baltimore Medical Center, 2019)
We are reporting a rare case of acupuncture-related acute pericarditis in an old-aged gentleman due to Staphylococcus aureus infection who was successfully managed with drainage of pericardial fluid and broad-spectrum antibiotics. We also reviewed the literature and found cardiac tamponade as the most common acupuncture-related cardiac complication, followed by infective endocarditis, bacterial abscess, and infected myxoma. There was no available literature on post-acupuncture acute pericarditis.